Iron handling by the human kidney: glomerular filtration and tubular reabsorption both contribute to urinary iron excretion - van Raaij, Sanne E. G.; Rennings, Alexander J.; Biemond, Bart J.; Schols, Saskia E. M.; Wiegerinck, Erwin T. G.; Roelofs, Hennie M. J.; Hoorn, Ewout J.; Walsh, Stephen B.; Nijenhuis, Tom; Swinkels, Dorine W.; van Swelm, Rachel P. L. (American journal of physiology. Renal physiology, 2019)
In physiological conditions, circulating iron can be filtered by the glomerulus and is almost completely reabsorbed by the tubular epithelium to prevent urinary iron wasting. Increased urinary iron concentrations have been associated with renal injury. However, it is not clear whether increased urinary iron concentrations in patients are the result of increased glomerular iron filtration and/or insufficient tubular iron reabsorption and if these processes contribute to renal injury. We measured plasma and urine iron parameters and urinary tubular injury markers in healthy human subjects ( n = 20), patients with systemic iron overload ( n = 20), and patients with renal tubular dysfunction ( n = 18). Urinary iron excretion parameters were increased in both patients with systemic iron overload and tubular dysfunction, whereas plasma iron parameters were only increased in patients with systemic iron overload. In patients with systemic iron overload, increased urinary iron levels were associated with elevated circulating iron, as indicated by transferrin saturation (TSAT), and increased body iron, as suggested by plasma ferritin concentrations. In patients with tubular dysfunction, enhanced urinary iron and transferrin excretion were associated with distal tubular injury as indicated by increased urinary glutathione S-transferase pi 1-1 (GSTP1-1) excretion. In systemic iron overload, elevated urinary iron and transferrin levels were associated with increased injury to proximal tubules, indicated by increased urinary kidney injury marker 1 (KIM-1) excretion. Our explorative study demonstrates that both glomerular filtration of elevated plasma iron levels and insufficient tubular iron reabsorption could increase urinary iron excretion and cause renal injury.